Dietary Threonine Supplementation for Improving Growth Performance and Edible Carcass Parts in Japanese Quails, Coturnix coturnix Japonica - Baylan, Mikail; Canogullari, Sibel; Ayasan, Tugay; Sahin, Ahmet (International Journal of Poultry Science, 2006)
The present study was conducted to evaluate the effects of dietary threonine amino acid supplementation on growth performance and carcass characteristics of Japanese quails. Day old, two hundred and seventy quail chicks were divided into six dietary treatment groups comprising 45 birds each, which consisted of 3 subgroups containing 15 birds for each replicate. Experimental diets were prepared and contained 0.81, 0.86, 0.91, 0.96, 1.01 and 1.06 % threonine amino acid, respective to groups 1-6, on fresh matter basis. Birds were fed these experimental diets respective to treatment for 35 days. Total feed intakes and the changes in body weights were determined on weekly basis. At the end of experiment 35-d, birds were killed humanly to determine their edible carcass parts. Results showed that threonine supplementation to the diet did not affect growth performance and edible carcass parts (p>0.05), assuming that birds can make metabolic adaptation to current dietary threonine supplementations.